Aging in Place Through the COVID-19 Pandemic: Perspectives from Aging Service Providers. (July 2023) - Greer, Valerie; Canham, Sarah L.; Hong, Andy; Agutter, James; Garcia Zambrana, Ivis; Van Natter, Jess M.
Formal and informal networks of resources are critical to supporting the growing number of older adults aging in place (AIP). Data are needed from aging-service providers about assets and barriers that impact their abilities to support AIP during the pandemic, as well as emergent needs resulting from response measures. A series of World Café workshops were conducted with aging-service providers in Salt Lake City, Utah, to understand supportive factors, service gaps, and future needs. Novel domains to support AIP in the context of the pandemic were identified: digital access and literacy, social isolation and mental health, and emergency preparedness. Issues related to access, equity, and affordability were identified as overarching themes across domains. Issues reflect concern over how the pandemic exacerbated socioeconomic and cultural disparities impacting older adults who benefit from aging services. Networks of advocacy and support are needed to bolster resources for older adults, caregivers, and aging-service providers.